2009
DOI: 10.1016/j.bpc.2008.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid structure and sequence probing using fluorescent base analogue tCO

Abstract: The fluorescent cytosine analog tC(O) is on average the brightest probe of its kind and, moreover, it introduces minimal perturbations to the normal secondary structure of DNA. Here several ways of how tC(O), with an advantage, can be used as a local fluorescent probe in nucleic acid systems are presented. Most importantly, we show that tC(O) is an excellent probe for the detection of individual melting processes of complex nucleic acid structures containing a large number of separate secondary structure motif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The lifetime of tC o fluorescence depends largely on its local environment. (4546) We assume that, in a pol-P/T binary complex, the majority of SeqB1 will be in the pol domain, and the majority of SeqB3 will be in the exo domain. If minor-groove HB interactions are important for keeping a P/T in the pol domain, then the local environment of tC o in SeqB2 will resemble that of tC o in SeqB1, otherwise, it will be closer to that of tC o in SeqB3.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…The lifetime of tC o fluorescence depends largely on its local environment. (4546) We assume that, in a pol-P/T binary complex, the majority of SeqB1 will be in the pol domain, and the majority of SeqB3 will be in the exo domain. If minor-groove HB interactions are important for keeping a P/T in the pol domain, then the local environment of tC o in SeqB2 will resemble that of tC o in SeqB1, otherwise, it will be closer to that of tC o in SeqB3.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…It is not surprising that both the replacement of the primary amine of cytosine by a secondary amine and the attachment of an additional aromatic ring alter the electronic character of the N 4 nitrogen. Indeed, we recently reported that a DNA oligonucleotide containing a tC O : A mismatch is significantly more stable than the corresponding duplex with a tC O :T or tC O :C mismatch (51). Moreover, the emission spectrum of the duplex with the tC O :A mismatch exhibited a characteristic fine structure that may point towards firmer base stacking, a change in the polarity of the surroundings, a wobble A + : C base pair resulting from the protonation of adenine at N-1 or hydrogen tautomerisation from the nitrogen at N 4 (pyrimidine numbering) to N-3 of tC O .…”
Section: Resultsmentioning
confidence: 99%
“…In a 10 base pair duplex, changing the base pair partner with tCo gave T M s of tCo-G 46 °C, tCo-A 34 °C, tCo-T 24 °C and tCo -C 20°C. Thus, the tCo-A mismatch is significantly more stable than the other mismatches (41). The fluorescence emission spectrum also mirrors the special character of the tCo-A base pair.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence emission spectrum also mirrors the special character of the tCo-A base pair. It exhibits a fine structure that could be indicative of a stabilized imino tautomer, besides other structural rearrangements (41). Interestingly, the thermodynamic mismatch stabilities correlate with the order of mismatch discrimination by pol α and KF.…”
Section: Discussionmentioning
confidence: 99%